IMPROVING THE MOTOR ACTIVITY OF HIGHLY QUALIFIED FOOTBALL PLAYERS IN CHINA TAKING INTO ACCOUNT THE VARIATION OF THE INTENSITY OF TRAINING AT SMALL VENUES - Yaci, Lin; Polishkis, M.M.; Pleshakov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of the methodology for improving the motor activity of highly qualified female football players in China, taking into account the variation in the intensity of training at small venues. Methods and structure of the study. The experiment was conducted in 2020-2022, in which the girls of the Chinese women’s national football team and professional clubs participating in the games of the Chinese Women’s Super League took part. The age of the participants was 20-25 years. The study included approbation of the effectiveness of the use of small areas to increase the motor activity of female football players during the game, which was assessed by the dynamics of indicators of quantitative and qualitative characteristics of the game actions of female athletes in the process of competitive activity. Results and conclusions. The methodology for increasing the motor activity of highly qualified female football players in China, taking into account the variation in the intensity of training on small venues, includes many components, factors and various forms of improvement in real game conditions that determine the effectiveness of the development of aerobic and anaerobic endurance, speed abilities, as well as technical and tactical actions and interactions . To increase the motor activity of highly qualified female football players in the process of competitive activity through the mechanism of increasing speed and endurance, it is necessary to pay special attention to the issues of aerobic and anaerobic performance. This approach is a solid basis for improving athletic performance and serves as an important basis for improving physical fitness.